Les diplômés de l'immersion: implications dans le domaine de l'enseignement du français - Wesche, Marjorie Bingham (Canadian Journal of Higher Education, 1989)
This paper reports the results of three studies relating to French immersion graduates in the Ottawa area. The first study concerns post-secondary offerings in French for second language speakers. Conducted at four universities which receive the largest number of these students, Ottawa, Carleton, Queen's and McGill, it describes a variety of courses, programs and services in French available as early as ¡985. The second study surveyed all first-year anglophone students at the University of Ottawa in 1987 on their background and future intentions regarding French language study. It revealed that over 20% had studied in French immersion programs and that there was considerable interest in further French study. The third study was a longitudinal follow-up of immersion graduates in the four universities between 1985 and 1988. It showed that upon beginning university studies, they had very high functional abilities in French (although not native-like), and that these skills were maintained during their university studies. However, in first as well as third year, they reported using French very little outside class and taking only a few classes in it. Starting from the idea expressed by students in both studies that they avoid courses in French for fear of getting lower grades or because they have very restricted electives in their academic programs, the author suggests changes in terms of course offerings and at the administrative level to encourage these students to take more courses in French.